Corporate Disclosure and Firm Characteristics: A Puzzling Relationship - Foued Khlifi; Abdelfettah Bouri (Journal of Accounting, Business and Management (JABM), 2010)
The findings of prior studies on the determinants of corporate disclosure, in annual reports or websites, do not seem to be unequivocal. The aim of this paper is to show, theoretically, that mixed results are due to some methodological problems. After discussing of different theoretical explanations of corporate disclosure, we conclude that there is not a definite theory conceived to explain the reasons that stimulate voluntary disclosure. Consequently, we can affirm that the larger number of theories used by researchers in accounting and finance to explain this practice account for the mixed results shown by prior empirical studies. In the current paper, however, we defend the assumption according to which the mixed results of the previous studies on the determinants of corporate disclosure are due to some methodological problems. Thus, the previous studies assume that the relationship between the disclosure level and its determinants is known. Nevertheless, the results of the empirical studies on the determinants of corporate disclosure confirm that it is a naive assumption. As a result, we suggest refusing the conventional methods of statistical analysis.